PENEGAKAN HUKUM TERHADAP PENCEMARAN LINGKUNGAN HIDUP ATAS LIMBAH BATUBARA DI SUNGAI DESA PENANDING KABUPATEN BENGKULU TENGAH - Mona Agustina Nedy (JURNAL HUKUM DAS SOLLEN, 2025)
Environmental changes are largely determined by human attitudes and protection of their environment. Utilization of natural resources, both biological and non-biological, greatly affects environmental conditions and can even disrupt the balanced life system between life itself and its environment. Coal waste found in the Bengkulu River in Penanding Village, Central Bengkulu is used as an opportunity by the community, especially those living on the riverbanks as a livelihood. Law enforcement against environmental pollution due to coal waste in the Penanding Village River, Central Bengkulu Regency must be followed up by law enforcement officials. This research approach uses qualitative descriptive data analysis techniques or by describing the data obtained from the results of field research and library research into descriptions so that in the end it can answer the problem. The analysis of this research is analyzed qualitatively. Based on the analysis of the discussion, there has been no follow-up action regarding law enforcement against environmental pollution due to coal waste in the Penanding Village River, Central Bengkulu Regency regarding environmental pollution caused by coal waste. Obstacles include legal factors or statutory regulations, law enforcement factors, permits, overlapping and competing interests, institutional obstacles, environmental impact analysis systems and inadequate facilities and infrastructure.